A kind of reconstituted wood and preparation method thereof
Through the optimization of the process and the use of modified phenolic resin, the problem of low efficiency of the glue dipping process in the production of recombinant wood is solved, and efficient production and product performance are achieved.
Patent Information
- Application Number
- CN202211683660.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-27
AI Technical Summary
In the existing industrial recombinant wood production process, the double drying caused by the glue impregnation process is high in consumption, low production efficiency, and it is difficult to achieve continuous production.
By optimizing the thickness, moisture content, synthesis method of modified phenolic resin, glue application method, blank pre-pressing and hot pressing forming processes, the dissolution, post-gluing drying and balanced treatment processes are reduced, and the coating of modified phenolic resin is adopted. and hot press forming process.
The production efficiency of the recombinant wood manufacturing process has been greatly improved, continuous production has been achieved, and the hardness, wear resistance, fire resistance and aesthetics of the product have been improved.
Smart Images

Figure CN116061272B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wood processing, in particular to reconstituted wood and a preparation method thereof. Background Art
[0002] Reconstructed wood is made by processing and recombining artificial fast-growing wood without disrupting the fiber arrangement direction and retaining the basic characteristics of the wood. It is manufactured into a new type of wood with controllable performance, adjustable specifications, designable structure and natural wood grain structure. It is one of the important ways to efficiently and high-quality utilize low-quality wood.
[0003] The existing industrial reconstituted wood production process is to spin (planer) logs into veneer strips, then decompose them into fiberized wood veneers, or directly decompose logs into wood bundles, and then dry, dip, dry after glue, balance, assemble, and glue to form a wood composite material. The dip process requires the fiberized wood veneer or wood bundle to be dried twice before and after dipping, which not only consumes a lot of energy, but also seriously affects the production efficiency. In particular, the drying after dipping must ensure a high drying efficiency and prevent the resin from pre-curing. Usually, the drying temperature needs to be controlled below 70°C. At this drying temperature, the saturated fiberized wood veneer or wood bundle needs to be dried to a final moisture content of 8% to 15%, which takes 3 to 10 hours, and the production efficiency is low. In addition, after drying, the fiberized veneer or wood bundle has uneven moisture content between boards or within the board, and needs to be balanced for 1 to 2 days. Therefore, it is difficult to form a continuous production line. Summary of the invention
[0004] The purpose of the present invention is to provide a reconstituted wood and a preparation method thereof to solve the problems existing in the prior art. The present invention reduces the processes of debonding, post-gluing drying and balancing treatment in the manufacturing process of reconstituted wood by optimizing the veneer thickness, veneer moisture content, adhesive synthesis method, gluing method, assembly pre-pressing and hot pressing molding process, thereby greatly improving production efficiency and helping to achieve continuous production.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is: a reconstituted wood, which is formed by pressing and assembling single board strips (basic units) coated with modified phenolic resin (adhesive) along the grain;
[0007] The modified phenolic resin comprises the following raw materials in parts by weight: 100 parts of phenol, 90-130 parts of 50wt.% formaldehyde aqueous solution, 2-6 parts of boric acid, 6-18 parts of alkaline compounds and 0.5-4.5 parts of acidic compounds.
[0008] Furthermore, the length of the veneer strip is 1300-2650 mm, the thickness is 0.8-1.5 mm, and the width is 300-1300 mm; the density of the reconstituted wood is 0.65-0.95 g / cm 3 .
[0009] The second technical solution of the present invention is a method for preparing the above-mentioned recombinant wood, comprising the following steps:
[0010] (1) After the logs are peeled into veneers, they are cut and dried to obtain veneer strips;
[0011] (2) coating the surface of the veneer strip with a modified phenolic resin, and then assembling the veneer strips along the grain and pre-pressing them to obtain a reconstituted wood board;
[0012] (3) hot pressing the reconstituted wood blank to obtain the reconstituted wood.
[0013] Furthermore, in step (1), the drying temperature is 80-110° C.; and the moisture content of the veneer strip is 2-6%.
[0014] Furthermore, in step (2), the preparation method of the modified phenolic resin specifically comprises:
[0015] Weigh the raw materials according to the above weight proportions, mix phenol, boric acid and the first batch of 50wt.% formaldehyde aqueous solution and stir evenly, adjust the pH to 1-4, heat and reflux to react, then add the alkaline compound and the second batch of 50wt.% formaldehyde aqueous solution, heat and react, finally add the acidic compound to make the pH of the system 6-8, cool to 10-40°C, and obtain the modified phenolic resin;
[0016] The molar ratio of formaldehyde to phenol in the first batch of 50 wt. % formaldehyde aqueous solution is (0.5-1.0):1.
[0017] Furthermore, after the second batch of 50 wt. % formaldehyde aqueous solution is added, the molar ratio of total formaldehyde to phenol in the system is (1.3-2.2):1.
[0018] Furthermore, the heating reflux reaction time is 1 to 3 hours; the heating reaction temperature is 60 to 90° C., and the time is 2 to 5 hours.
[0019] Furthermore, the alkaline compound is a monovalent metal compound; and the acidic compound is boric acid and / or phosphoric acid.
[0020] Furthermore, the alkaline compound is sodium hydroxide and / or potassium hydroxide.
[0021] Advantages of modified phenolic resin: good low-temperature stability, molecular weight remains basically unchanged during the pre-pressing stage, and good permeability is maintained. At the same time, the resin uses boric acid as a modifier, and the acidic compound is boric acid and / or phosphoric acid (boron-containing and / or phosphorus-containing compounds), which makes the resin have good fire resistance. In addition, the resin also has the advantage of light color and can well retain the original color and texture of the wood.
[0022] Furthermore, in step (2), the coating amount of the modified phenolic resin is 8-20% of the weight of the absolute dry single board strip; the pre-pressing temperature is 60-80°C, the time is 30-240 minutes, and the pressure is 0.5-2.5MPa.
[0023] Furthermore, in step (3), the hot pressing temperature is 125-145° C., the time is 1.2-2.0 min / mm, and the pressure is 2.5-4.5 MPa.
[0024] The time of 1.2 to 2.0 min / mm means that according to the thickness of the slab, the pressing time is 1.2 to 2.0 minutes for each millimeter. For 20 mm thick reconstituted wood, the pressing time is 24 to 40 minutes.
[0025] Furthermore, in step (2), the coating method is roller coating or spraying.
[0026] Furthermore, the logs include any one of poplar logs, eucalyptus logs, and red cone logs.
[0027] The third technical solution of the present invention: an application of the above-mentioned reconstituted wood in the preparation of floors, furniture, doors and windows.
[0028] The present invention synthesizes a modified phenolic resin by a specific synthesis process and by adding a modifier. During the pre-pressing process (temperature is 60-80°C), the molecular weight remains substantially unchanged, and as the temperature increases, the viscosity decreases, and the permeability of the adhesive is greatly improved. Therefore, the penetration of the adhesive can be achieved during the pre-pressing process, which changes the problem that the adhesive needs to be impregnated in the traditional reconstituted wood manufacturing process and is completed under the action of a large amount of water, reduces the drying and moisture content balance process of the fiberized wood veneer or wood bundle glue, and improves production efficiency.
[0029] The present invention discloses the following technical effects:
[0030] (1) The reconstituted wood of the present invention has high hardness, wear resistance, beautiful texture, fire resistance, and is not easy to crack, and can meet the performance requirements of indoor and outdoor engineering materials.
[0031] (2) The present invention aims to solve the technical problems of low efficiency and difficulty in continuous production of traditional reconstituted wood, and provides a method for preparing reconstituted wood. By optimizing the veneer thickness, veneer moisture content, phenolic resin performance, gluing method, pre-pressing of assembly and hot pressing molding process, the process of reconstituted wood manufacturing is reduced, such as debonding, post-gluing drying and balancing treatment, which greatly improves the production efficiency and helps to achieve continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 The process flow chart of preparing recombinant wood of the present invention;
[0034] Figure 2 This is a physical picture of the poplar wood recombinant wood prepared in Example 1 of the present invention;
[0035] Figure 3 The figure is a comparison of the wear resistance of the poplar wood recombinant wood prepared in Example 1 of the present invention and in Comparative Example 1, wherein (A) is a poplar log, (B) is a poplar wood recombinant wood prepared in Example 1, and (C) is a poplar wood recombinant wood prepared in Comparative Example 1;
[0036] Figure 4 This is a physical picture of the eucalyptus recombinant wood prepared in Example 2 of the present invention;
[0037] Figure 5 This is a physical picture of the recombinant Castanopsis hystrix wood prepared in Example 4 of the present invention;
[0038] Figure 6 This is a physical picture of the poplar wood reconstituted wood prepared in Example 1 of the present invention used as an outdoor floor;
[0039] Figure 7 This is a physical picture of the poplar wood reconstituted wood prepared in Comparative Example 1 of the present invention as an outdoor floor;
[0040] Figure 8 The rheological curves of the phenolic resins prepared in Example 1 and Comparative Example 1 of the present invention at 80°C are shown. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] The “parts” described in the following examples are all “parts by weight”.
[0047] A method for preparing reconstituted wood:
[0048] (1) Preparation of modified phenolic resin: Phenol, boric acid and the first batch of 50 wt.% formaldehyde aqueous solution are mixed and stirred uniformly, the pH is adjusted to 1-4, and heated to reflux for 1-3 hours; after the reaction is completed, an alkaline compound and a second batch of 50 wt.% formaldehyde aqueous solution are added, and the reaction is carried out at 60-90° C. for 2-5 hours; after the reaction is completed, an acidic compound is added to adjust the pH of the system to 6-8, and the system is cooled to 10-40° C. to obtain a modified phenolic resin.
[0049] (2) Cutting the logs and then peeling them to obtain veneers, cutting and drying the veneers to obtain veneer strips, applying glue (modified phenolic resin) to the veneer strips, measuring and assembling them along the grain, and then pre-pressing and hot-pressing to obtain reconstituted wood; the process flow chart for preparing reconstituted wood is shown in Figure 1 .
[0050] The modified phenolic resin comprises the following raw materials in parts by weight: 100 parts of phenol, 90-130 parts of 50wt.% formaldehyde aqueous solution, 2-6 parts of boric acid, 6-18 parts of alkaline compounds and 0.5-4.5 parts of acidic compounds.
[0051] The molar ratio of formaldehyde to phenol in the first batch of 50 wt. % formaldehyde aqueous solution is (0.5-1.0):1; after the second batch of 50 wt. % formaldehyde aqueous solution is added, the molar ratio of total formaldehyde to phenol in the system is (1.3-2.2):1.
[0052] The alkaline compound is sodium hydroxide and / or potassium hydroxide; the acidic compound is boric acid and / or phosphoric acid.
[0053] The length of the veneer strip is 1300-2650mm, the thickness is 0.8-1.5mm, and the width is 300-1300mm; the density of the reconstituted wood is 0.65-0.95g / cm 3 .
[0054] The drying temperature is 80-110°C; the moisture content of the single board strip is 2-6%.
[0055] The coating amount of the modified phenolic resin is 8 to 20% of the weight of the absolute dry single board strip;
[0056] The pre-pressing temperature is 60-80°C, the time is 30-240min, and the pressure is 0.5-2.5MPa; the hot pressing temperature is 125-145°C, the time is 1.2-2.0min / mm, and the pressure is 2.5-4.5MPa.
[0057] The glue is applied by roller coating or spraying.
[0058] Example 1
[0059] A method for preparing poplar recombinant wood:
[0060] (i) Preparation of adhesive: 100 parts of phenol, 4 parts of boric acid and 45 parts of 50 wt.% formaldehyde aqueous solution (the molar ratio of formaldehyde to phenol is 0.70:1) are mixed and stirred uniformly, the pH is adjusted to 3, and heated to reflux for 2 hours; after the reaction is completed, 10 parts of sodium hydroxide and 65 parts of 50 wt.% formaldehyde aqueous solution (the molar ratio of total formaldehyde to phenol in the system is 1.72:1) are added, and the reaction is carried out at 80°C for 3 hours; after the reaction is completed, 1 part of boric acid is added, and the mixture is cooled to 10-40°C to obtain a modified phenolic resin with a solid content of 65%, a viscosity of 260 cps, and a pH of 7.9.
[0061] (ii) Veneer peeling: The poplar logs are cut into wood segments with a length of 2650 mm, and then the wood segments are peeled into veneers with a thickness of 1.5 mm using a peeling machine. Finally, the veneers are cut into wet veneer strips with a width of 1300 mm.
[0062] (III) Single-strip drying: The wet single-strip is dried using a mesh belt dryer (drying temperature is 80° C.) until the moisture content is 3%, thereby obtaining single-strip.
[0063] (iv) Gluing of veneer: The modified phenolic resin prepared in step (i) is evenly coated on the surface of the veneer strip by gluing (gluing), so that the coating amount of the modified phenolic resin is 20% of the weight of the absolute dry veneer strip.
[0064] (V) Assembly pre-pressing: The veneer strips after gluing are pre-pressed according to the density of 0.95g / cm 3 After metering and weighing, the wood is assembled along the grain and then sent to a pre-pressing machine for pre-pressing. The pre-pressing temperature is 80°C, the pre-pressing time is 30 minutes, and the pre-pressing pressure is 0.5 MPa to obtain a reconstituted wood board.
[0065] (VI) Hot Pressing: The reconstituted wood blank is sent into a hot press for hot pressing at a temperature of 145°C, a time of 24 minutes, and a pressure of 3.0 MPa.
[0066] The actual picture of the poplar wood recombinant wood prepared in this embodiment is shown in Figure 2 The physical and mechanical properties are shown in Table 1. All physical and mechanical properties have reached the outdoor material performance index requirements of the forestry industry standard "Reconstructed Wood" (draft for approval). Figure 3 (B), and poplar logs (see Figure 3 Compared with (A), the wear resistance is significantly improved.
[0067] Comparative Example 1
[0068] The same as Example 1, except that the adhesive preparation method in step (a) is as follows: 100 parts of phenol and 45 parts of 50wt.% formaldehyde aqueous solution are mixed and stirred uniformly, the pH is adjusted to 3, and heated to reflux for 2h; after the reaction is completed, 10 parts of sodium hydroxide and 65 parts of 50wt.% formaldehyde aqueous solution are added, and the reaction is carried out at 80°C for 3.0h; after the reaction is completed, the mixture is cooled to 10-40°C to obtain a phenolic resin with a solid content of 63%, a viscosity of 240cps, and a pH of 11.0.
[0069] The performance defects of the poplar wood recombinant wood prepared in this comparative example are: dark color, rapid molecular weight growth at 80℃; Figure 3 (C), with obvious wear marks.
[0070] The physical and mechanical properties of the poplar recombinant wood prepared in Example 1 and Comparative Example 1 are compared, and the results are shown in Table 1.
[0071] Table 1 Physical and mechanical properties of poplar reconstituted wood
[0072]
[0073] The thickness of the poplar recombinant wood prepared in Comparative Example 1 is 20 mm, and the physical and mechanical properties are shown in Table 1. Most of the physical and mechanical properties do not meet the performance index requirements of the forestry industry standard "Recombinant Wood" (draft for approval).
[0074] It can be seen from Table 1 that the ignition time of Example 1 was extended by 1.5 times, the peak heat release rate within 300 s and the total heat release within 300 s (pHRR.0) decreased by 39.5% and 35.7% respectively, and reached Class B1.
[0075] Example 2
[0076] A method for preparing eucalyptus recombinant wood:
[0077] (i) Preparation of adhesive: 100 parts of phenol, 6 parts of boric acid and 34 parts of 50 wt.% formaldehyde aqueous solution (the molar ratio of formaldehyde to phenol is 0.53:1) are mixed and stirred uniformly, the pH is adjusted to 2, and heated to reflux for 3 hours; after the reaction is completed, 15 parts of sodium hydroxide and 60 parts of 50 wt.% formaldehyde aqueous solution (the molar ratio of total formaldehyde to phenol in the system is 1.47:1) are added, and the reaction is carried out at 85°C for 3.5 hours; after the reaction is completed, 2 parts of boric acid are added, and the mixture is cooled to 10-40°C to obtain a modified phenolic resin with a solid content of 69%, a viscosity of 300 cps, and a pH of 6.5.
[0078] (ii) Veneer peeling: The eucalyptus logs are cut into wood segments with a length of 2000 mm, and then the wood segments are peeled into veneers with a thickness of 1.20 mm using a peeling machine, and finally the veneers are cut into wet veneer strips with a width of 300 mm.
[0079] (III) Single-strip drying: The wet single-strip is dried using a mesh belt dryer (drying temperature is 110° C.) until the moisture content is 5% to obtain single-strip.
[0080] (iv) Gluing of veneer: The modified phenolic resin prepared in step (i) is evenly applied on the surface of the veneer strip by spraying (gluing), so that the coating amount of the modified phenolic resin is 8% of the weight of the absolutely dry veneer strip.
[0081] (V) Assembly pre-pressing: The veneer strips after gluing are pre-pressed according to the set density of 0.65g / cm 3 After metering and weighing, the wood is assembled along the grain and then sent to a pre-pressing machine for pre-pressing. The pre-pressing temperature is 60°C, the pre-pressing time is 30 minutes, and the pre-pressing pressure is 1.1 MPa to obtain a reconstituted wood board.
[0082] (VI) Hot Pressing: The reconstituted wood blank is sent into a hot press for hot pressing, and is pressed into a density of 0.65 g / cm 3Eucalyptus recombinant wood, hot pressing temperature is 125℃, hot pressing time is 2.0min / mm, and hot pressing pressure is 2.5MPa.
[0083] Figure 4 This is a real picture of the eucalyptus reconstituted wood prepared in this example. After testing, the physical and mechanical properties are shown in Table 2. All physical and mechanical properties meet the performance index requirements of indoor reconstituted wood in the forestry industry standard "Reconstituted Wood" (draft for approval).
[0084] Comparative Example 2
[0085] Same as Example 2, except that a conventional phenolic resin is used as an adhesive, with a solid content of 48%, a viscosity of 300 cps, and a pH of 12.
[0086] After testing, the thickness of eucalyptus reconstituted wood is 20mm, and its physical and mechanical properties are shown in Table 2. The water absorption thickness expansion rate, width expansion rate, horizontal shear strength, static bending strength and other indicators do not meet the performance index requirements of indoor reconstituted wood in the forestry industry standard "Reconstituted Wood" (draft for approval).
[0087] The physical and mechanical properties of the eucalyptus recombinant wood prepared in Example 2 and Comparative Example 2 are compared, and the results are shown in Table 2.
[0088] Table 2 Physical and mechanical properties of eucalyptus reconstituted wood
[0089]
[0090]
[0091] It can be seen from Table 2 that the ignition time of Example 2 was extended by 3.5 times, and the peak value of the heat release rate within 300 s and the total amount of heat released within 300 s decreased by 18.4% and 36.3% respectively.
[0092] Example 3
[0093] A preparation method of Castanopsis hystrix recombinant wood:
[0094] (i) Preparation of adhesive: 100 parts of phenol, 4 parts of boric acid and 60 parts of 50 wt.% formaldehyde aqueous solution (the molar ratio of formaldehyde to phenol is 0.94:1) are mixed and stirred uniformly, the pH is adjusted to 3.5, and heated to reflux for 1.5 hours; after the reaction is completed, 6.5 parts of sodium hydroxide and 70 parts of 50 wt.% formaldehyde aqueous solution (the molar ratio of total formaldehyde to phenol in the system is 2.04:1) are added, and the reaction is carried out at 65°C for 4.5 hours; after the reaction is completed, 1.2 parts of boric acid are added, and the mixture is cooled to 10-40°C to obtain a modified phenolic resin with a solid content of 62%, a viscosity of 200 cps, and a pH of 7.5.
[0095] (ii) Veneer peeling: Cut the red cone logs into wood segments with a length of 2000 mm, then use a peeling machine to peel the wood segments into veneers with a thickness of 0.8 mm, and finally cut the veneers into wet veneer strips with a width of 300 mm.
[0096] (III) Single-strip drying: The wet single-strip is dried using a mesh belt dryer (drying temperature is 110° C.) until the moisture content is 3% to obtain single-strip.
[0097] (iv) Gluing of veneer: The modified phenolic resin prepared in step (i) is evenly coated on the surface of the veneer strip by gluing (gluing), so that the coating amount of the modified phenolic resin is 15% of the weight of the absolute dry veneer strip.
[0098] (V) Assembly pre-pressing: The veneer strips after gluing are pre-pressed according to the density of 0.85g / cm 3 After metering and weighing, the wood is assembled along the grain and then sent to a pre-pressing machine for pre-pressing. The pre-pressing temperature is 70°C, the pre-pressing time is 240 minutes, and the pre-pressing pressure is 1.5 MPa to obtain a reconstituted wood board.
[0099] (VI) Hot Pressing: The reconstituted wood board is fed into a hot press for hot pressing at a temperature of 135° C., a time of 90 min, and a pressure of 2.0 MPa.
[0100] Figure 5 This is a photo of the reconstituted red cone wood prepared in this example. After testing, the thickness of the reconstituted red cone wood is 40 mm and the density is 0.85 g / cm 3 , moisture content is 12%, 28h circulating water boiling water absorption thickness expansion rate is 8.5%, water absorption width expansion rate is 3.2%, horizontal shear strength is 24MPa, static bending strength is 132MPa, oxygen index is 24.6%, and various physical and mechanical properties have met the outdoor material performance index requirements of the forestry industry standard "Reconstructed Wood" (draft for approval).
[0101] Example 4
[0102] The same as Example 1, except that the preparation method of the adhesive in step (a) is as follows: 100 parts of phenol, 4 parts of boric acid and 45 parts of 50wt.% formaldehyde aqueous solution (the molar ratio of formaldehyde to phenol is 0.70:1) are mixed and stirred uniformly, the pH is adjusted to 1.5, and heated to reflux for 2h; after the reaction is completed, 18 parts of sodium hydroxide and 85 parts of 50wt.% formaldehyde aqueous solution (the molar ratio of total formaldehyde to phenol in the system is 2.04:1) are added, and the reaction is carried out at 70°C for 4h; after the reaction is completed, 4.2 parts of boric acid are added, and the mixture is cooled to 10-40°C to obtain a modified phenolic resin with a solid content of 64%, a viscosity of 240cps, and a pH of 6.9.
[0103] Effect Example 1
[0104] The poplar wood recombinant wood prepared in Example 1 of the present invention and Comparative Example 1 was laid outdoors as outdoor flooring. The changes of the flooring were observed after laying for 2 months. The results show that Figure 6 and Figure 7 .
[0105] from Figure 6 and Figure 7 It can be seen that the poplar wood recombinant wood prepared in Example 1 of the present invention does not crack when used as outdoor flooring, while the poplar wood recombinant wood prepared in Comparative Example 1 cracks when laid outdoors.
[0106] Effect Example 2
[0107] The rheological curves of the phenolic resins prepared in Example 1 and Comparative Example 1 at 80°C were measured. Figure 8 .
[0108] Figure 8 In the figure, 1 is the rheological curve of the modified phenolic resin prepared in Example 1 at 80°C, and 2 is the rheological curve of the phenolic resin prepared in Comparative Example 1 at 80°C.
[0109] from Figure 8 It can be seen that, when tested at 80°C for 60 min, the shear viscosity of the modified phenolic resin prepared in Example 1 increases very slowly, indicating that the molecular weight of the phenolic resin changes very little, while the shear viscosity of the phenolic resin prepared in Comparative Example 1 increases rapidly, indicating that the molecular weight of the phenolic resin has increased significantly.
[0110] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A reconstituted wood, characterized in that: The reconstituted wood is formed by pressing and assembling veneer strips coated with modified phenolic resin along the grain; The modified phenolic resin comprises the following raw materials in parts by weight: 100 parts of phenol, 90-130 parts of 50wt.% formaldehyde aqueous solution, 2-6 parts of boric acid, 6-18 parts of alkaline compounds and 0.5-4.5 parts of acidic compounds; The alkaline compound is sodium hydroxide and / or potassium hydroxide; the acidic compound is boric acid and / or phosphoric acid; The method for preparing the recombinant wood comprises the following steps: (1) After the log is peeled into veneers, the veneers are cut and dried to obtain veneer strips; the veneer thickness is 0.8 to 1.5 mm; the moisture content of the veneer strips is 2 to 6%; (2) coating the surface of the veneer strip with a modified phenolic resin, and then pre-pressing the veneer strip after assembling along the grain to obtain a reconstituted wood board; the coating amount of the modified phenolic resin is 8 to 20% of the weight of the dry veneer strip; the pre-pressing temperature is 60 to 80° C.; (3) hot pressing the reconstituted wood blank to obtain the reconstituted wood; the hot pressing temperature is 125-145° C.; the density of the reconstituted wood is 0.65-0.95 g / cm 3 ; The preparation method of the modified phenolic resin specifically comprises: Weigh the raw materials according to the above weight proportions, mix phenol, boric acid and the first batch of 50wt.% formaldehyde aqueous solution and stir evenly, adjust the pH to 1-4, heat and reflux to react, then add the alkaline compound and the second batch of 50wt.% formaldehyde aqueous solution, heat and react, finally add the acidic compound to make the pH of the system 6-8, and cool to obtain the modified phenolic resin; The molar ratio of formaldehyde to phenol in the first batch of 50 wt. % formaldehyde aqueous solution is (0.5-1.0):
1.
2. The recombinant wood according to claim 1, characterized in that: The length of the single board strip is 1300-2650 mm, and the width is 300-1300 mm.
3. The reconstituted wood according to claim 1, characterized in that: In step (1), the drying temperature is 80-110°C.
4. The recombinant wood according to claim 1, characterized in that: The heating reflux reaction time is 1 to 3 hours; the heating reaction temperature is 60 to 90° C., and the time is 2 to 5 hours.
5. The reconstituted wood according to claim 1, characterized in that: In step (2), the pre-pressing time is 30 to 240 minutes, and the pressure is 0.5 to 2.5 MPa.
6. The recombinant wood according to claim 1, characterized in that: In step (3), the hot pressing time is 1.2 to 2.0 min / mm, and the pressure is 2.5 to 4.5 MPa.
7. Use of the reconstituted wood according to any one of claims 1 to 6 in the preparation of floors, furniture, doors and windows.
Citation Information
Patent Citations
Preparation method of boron-containing phenolic resin for friction materials
CN102746479A
Preparation method for low-cost insulating phenolic resin laminated board resistant to moisture and heat
CN105773763A
Preparation method of novel scrimber
CN113070954A
